Immunotherapy in Non-Small Cell Lung Cancer With Actionable Mutations Other Than EGFR - Seegobin, Karan; Majeed, Umair; Wiest, Nathaniel; Manochakian, Rami; Lou, Yanyan; Zhao, Yujie (Frontiers in Oncology, 2021)
While targeted therapies are the current standard of care first line treatment for non-small cell lung cancer (NSCLC) with actionable mutations, the cancer cells inevitably acquire resistance to these agents over time. Immune check-point inhibitors (ICIs) have improved the outcome of metastatic NSCLC, however, the efficacy of ICIs in NSCLC with targetable drivers is largely unknown. In this manuscript, we reviewed the published data on ICI therapy in NSCLC with aberrant ALK, ROS1, BRAF, c-MET, RET and NTRK expressions. We reviewed the published data on ICI therapy in NSCLC with epidermal growth factor receptor (EGFR) mutation in a separate manuscript. The objective response rates (ORRs) for ICI treatment in lung cancers harboring the BRAF (0-54%) and c-MET (12-49%) alterations were comparable to non-mutant NSCLC, whereas the ORRs in RET fusion NSCLC (less than10% in all studies but one) and ALK fusion NSCLC (0%) were relatively low. The ORRs in a small number of ROS1 fusion (7 patients) and NTRK fusion (2 patients) NSCLCs were found to be 0-17% and 50%, respectively. In most of the studies, no clear correlation between treatment outcomes and PD-L1 expression or tumor mutation burden (TMB) was identified; furthermore, how to select patients with NSCLC harboring actionable mutations who will likely benefit from ICI treatment remains unknown.